The sources of wage growth in a developing country - Ioana Marinescu; Margaret Triyana (IZA Journal of Labor & Development, 2016)
What are the sources of wage growth in developing countries? In the USA, general labor market experience is the key source of wage growth, with job seniority playing a smaller role. By contrast, in Indonesia, the 10-year return to seniority is 24 to 28 %, which is higher than the return to experience. Furthermore, we estimate a 35 % return to 10 years of tenure in the formal sector, with no significant return to tenure in the informal sector. The difference in the sources of wage growth in Indonesia versus the USA may be a reflection of Indonesia's lower level of development.
Keywords: J3; O1; 330; Human capital; Informal labor market; Returns to tenure